CSC750: Compiler Construction / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
The construction of a compiler involves three important phases. The lexical analysis phase deals with the identifying of lexeme items, the syntax analysis phase determines the underlying structure of the source program and the code generation phase produces the machine code. Global and local optimizations phases are two optional phases where the compiler will be improved in space and time.